A study on factors affecting intention to quit among employees at Terengganu Equestrian Resort / Nur Syazwani Mohamad - Mohamad, Nur Syazwani (Faculty of Business and Management, 2012)
Project paper titled “Factor That Affecting Intention to Quit among Employees at Terengganu Equestrian Resort” is conducted as partial requirement to fulfil the requirement as needed by the Faculty of Business Management, University Technology Mara (UiTM). The purpose of this study is to identify the factors that influence intention to TER’s employees to quit, to identify the most influence factors to intention to quit among employees at Terengganu Equestrian Resort and also are there any significant relationship between independent variables and dependent variable. Analysis of the data about the most influence factors to intention to quit among employees at Terengganu Equestrian Resort shows that, most of the employees agreed that I know what my responsibility and also I receive clear explanations of what has to be done are was the most influence factors to intention to quit among employees. In addition, by using the Pearson correlation method, analysis from 80 respondents shows that there was a significant and positive relationship between intention to quit with role ambiguity, which the Pearson correlation are at 0.031.